POTENTIAL PHYTOCONSTITUENTS FROM NATURAL PRODUCTS FOR COMBATING AGAINST CORONAVIRUS DISEASE-19 (SEVERE ACUTE RESPIRATORY SYNDROME CORONAVIRUS‐2) - A REVIEW - R, CHANDRASEKAR; B, SIVAGAMI; KUMAR G, SATHEESH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Coronavirus called as coronavirus diseases (COVID)-19 (severe acute respiratory syndrome coronavirus [SARS‐CoV]‐2) is a viral infection which is spreading to a great extent and affecting many people worldwide, many developed and developing countries are severely affected by the virus. The World Health Organization (WHO) is taking serious preventive measures to stop this viral infection worldwide. The coronavirus is a big threat to human beings and controlling the emerging viral infections is a global concern. Antiviral drug such as Remdesivir has been approved by the FDA, but combating against these viral infections is a great challenge to scientists and researchers with the available few antiviral drugs due to severe side effects and toxicity. Many drugs such as hydroxy chloroquin, Remdesivir, and vaccines have been recommended for combating this virus. Few Polyherbal formulations and Ayurvedic formulations containing antiviral phytoconstituents have been recommended to boost the immunity. Some drugs and phytoconstituents are under different phases of human clinical trials. The currently available synthetic drugs and vaccines for the treatment of viral infections have severe side effects. Medicinal plants play a critical role in treating viral infections by developing immunity against viral diseases. Some medicinal plants which were used as antipyretic, analgesic, and anti-inflammatory activity helped in treating various diseases and viral infections. Many plants contain flavonoids such as quercetin, luteolin, apigenin, and polyphenols such as thymoquinone, phytosteroids such as cucurbitacin and others which may likely to act as antioxidants and immunomodulatory that can fight against COVID-19. The current review provides information on phytochemical constituents present in medicinal plants, their mechanism of action, in silico molecular docking studies and human clinical trials to treat viral disorders.